The Food Truck Phenomenon Among Millenials - Dian Christina Silalahi; Kurniawati (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2023)
This study aimed to examine the impact of Employee Friendliness, Food Quality, Food and Beverage Options, and Ambience on Customer Satisfaction and the frequency of eating through Word of Mouth mediation. The distribution of questionnaires was used in this study to obtain samples as analysis material to be processed. Purposive sampling was used to select 153 millennial customer respondents for the study, which was then analyzed using the SEM (Structural Equation Modelling) method. AMOS is used in this SEM method (Moment Structure Analysis). According to the findings of this study, there is a significant positive effect of Employee Friendliness on Overall Customer Satisfaction. Overall, Customer Satisfaction influences Word of Mouth positively. Dining Frequency is significantly influenced by word of mouth. Customer Satisfaction, mediated by word of mouth, significantly affects Dining Frequency. By conducting field surveys, producers and owners of food trucks are encouraged to improve food quality, variety of food sold, taste, and atmosphere to contribute to the growth and popularity of food trucks among millennials.